After exit: Academic achievement patterns of former English language learners. - de Jong, Ester J. (Education Policy Analysis Archives, 2004)
With few exceptions, accountability systems for programs for English language learners (ELLs) have focused on the achievement patterns of ELLs who are still considered “limited English proficient” and program evaluations have been unable to answer the question whether ELLs actually catch up with English proficient peers after attending a bilingual or English as a Second Language (ESL) program. Disaggregating data for former ELLs can therefore provide important information for long-term district and program accountability. The study was concerned with the achievement patterns in English language arts, Math, and Science of former ELLs who attended a bilingual and a English as a Second Language (ESL) program. It also explored whether length of program participation and grade level exited played a significant role in predicting academic achievement patterns for these exited students. Results indicate that 4th grade students more closely paralleled non- ELL students’ achievement patterns than 8th grade students, particularly for the BE students. While length of program participation is not a significant predictor of former ELLs’ academic success, exit grade does emerge as an important variable to take into consideration in setting exit guidelines.